Socio-economic drivers of bushmeat consumption in the northern Angolan province of Uíge - Lunis Giona Bolognino de Orth; Raffael Ernst; Mawunu Monizi; Thea Lautenschläger (Oryx)
The overexploitation of wildlife for bushmeat consumption poses a significant threat to biodiversity in sub-Saharan Africa, particularly in Angola, where the problem remains largely unexplored. This study provides the first overview of the regional bushmeat trade in Uíge Province and an analysis of consumption patterns in this socio-economic context. We provide data on the range of species hunted and their respective conservation status, and highlight the sources and structures underlying this regional trade. We conducted qualitative expert interviews with nine bushmeat traders from four communities and a quantitative consumer survey of 204 citizens of Uíge. More than 60% of the respondents consumed bushmeat at least once per week and 23% hunted regularly, indicating that this practice is deeply rooted in society. Of the 16 species sold in the central market in Uíge, five are categorized as threatened or Near Threatened on the IUCN Red List, highlighting the need for control measures. Large parts of the population consider bushmeat consumption to be an integral part of their culture but our results indicate that younger and better educated Angolans are moving away from these traditions and are less likely to practice traditional hunting. These findings suggest that access to comprehensive education and environmentally sustainable livelihoods is key to reducing the unsustainable use of wildlife resources.